Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Intervening - Ambrosius, Niko Ferdianto; Sari, Ayu Puspita; Rusliyawati, Rusliyawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the impact of GCG (Good Corporate Governance) on Firm Value, considering the role of Financial Performance as mediation. GCG is measured through the indicators of Managerial Ownership (MO) and Institutional Ownership (IO), while Firm Value is measured using Tobin’s Q, and Financial Performance is represented by Return on Equity (ROE). This study employs a quantitative approach, with sampling conducted using the Purposive Sampling technique. The research utilizes secondary data obtained from Fast-Moving Consumer Goods (FMCG) sector companies listed on the Indonesia Stock Exchange (IDX) and related company websites for the 2020–2024 period. Data analysis includes descriptive statistical tests, classical assumption tests, multiple linear regression, and path analysis using SPSS 25 software and the Sobel test calculator. The results indicate that GCG, proxied by Managerial Ownership and Institutional Ownership, does not have a significant effect on Firm Value and Financial Performance, as evidenced by the t-statistic values: Managerial Ownership (t-stat = 0.226 < t-table = 1.676) with a significance value of 0.791 > 0.05, and Institutional Ownership (t-stat = -0.999 < t-table = 1.676) with a significance value of 0.323 > 0.05. However, Financial Performance has a significant effect on Firm Value, as shown by the t-statistic (t-stat = -4.793 < t-table = 1.676) with a significance value of 0.000 < 0.05. Nevertheless, Financial Performance does not mediate the relationship between GCG and Firm Value.